Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China - Zhuang, Hailing; Yago, Masaya; Owada, Mamoru; Wang, Min (Zootaxa, 2017)
A total of 22 genera and 79 species of Thyatiridae (Insecta: Lepidoptera) from Yunnan, China are reviewed. Forty of these species are examined in detail, and the wing markings and genitalia of the male/female adults are illustrated. The following five species are recorded from Yunnan for the first time: Psidopala undulans (Hampson, [1893]), Tethea (Tethea) punctorenalia (Houlbert, 1921), Toxoides sichuanensis Zhuang, Owada & Wang, 2014, Mimopsestis basalis sinensis László, Ronkay, Ronkay & Witt, 2007 and Betapsestis brevis (Leech, 1900). Two new species, Parapsestis naxii sp. n. and Parapsestis tachengensis sp. n., are described and their DNA bar codes are provided using genbank accession number. Type species of genus Parapsestis, Parapsestis argenteopicta, we also provide its genbank accession number. Stenopsestis bruna Jiang, Yang, Xue & Han, 2015 is synonymized with Toxoides sichuanensis Zhuang, Owada & Wang, 2014. Biogeographical features of the family in Yunnan are also briefly discussed.